2015
DOI: 10.3109/0886022x.2015.1089464
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasminogen activator inhibitor-1 gene polymorphism and type 2 diabetic nephropathy

Abstract: Background: We investigated the relationship between plasminogen activator inhibitor-1 (PAI-1) 4G/5G insertion/deletion polymorphism and prevalence of diabetic nephropathy (DN) in Chinese patients. Methods: A total of 107 patients with type 2 diabetes were randomly recruited in the study, and 102 healthy subjects were selected as Control. Patients were divided into three groups according to their urinary albumin-creatinine ratio (UACR). Group A (n ¼ 44), had patients without DN (serum creatinine 5106 mmol/L an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…An increase of PAI-1 volume in plasma would lead to the reduction of fibrinolytic activity and hypercoagulability of the body [30], causing occlusion of vascular stenosis and occurrence of ischemic area in the blood wall. Xu et al revealed that PAI-1 levels were elevated in patients with type 2 diabetic nephropathy [31]. Additionally, our study also examined associations between inflammatory markers and clinical parameters in DPN patients, and revealed that PAI-1, TNF-a, and CRP levels were related to duration of disease, diabetic foot populations, HbA1c, FBG, TC, and TG in DPN patients.…”
Section: Discussionmentioning
confidence: 76%
“…An increase of PAI-1 volume in plasma would lead to the reduction of fibrinolytic activity and hypercoagulability of the body [30], causing occlusion of vascular stenosis and occurrence of ischemic area in the blood wall. Xu et al revealed that PAI-1 levels were elevated in patients with type 2 diabetic nephropathy [31]. Additionally, our study also examined associations between inflammatory markers and clinical parameters in DPN patients, and revealed that PAI-1, TNF-a, and CRP levels were related to duration of disease, diabetic foot populations, HbA1c, FBG, TC, and TG in DPN patients.…”
Section: Discussionmentioning
confidence: 76%
“…Plasminogen activator inhibitor-1 (PAI-1) serves an important role in the process of human cardiovascular diseases, which thereby leads to promotion of fibrinolysis (8,9). Xu et al (10) have recently demonstrated that PAI-1 gene polymorphism is associated with the development and progression of predominant proteinuria diabetes nephropathy. In addition, high plasma levels of thrombomodulin, PAI-1 and fibrinogen were detected in elderly, diabetic patients with depressive symptoms and further prospective larger studies are required to provide potential directions for future research, treatment and prevention of co-morbid depression and diabetes (8).…”
Section: Introductionmentioning
confidence: 99%
“…RPD occurs only in part of the children’s population because of serious inflammation. It is certain that PAI-1 genotype may be a predictor of progression of chronic renal disease ( 21 , 22 , 23 ). Study of Roelofs and colleagues in experimental animals (mice) had shown that PAI-1 is critically involved in host defense against Escherichia coli, modeled neutrophils influx and thus stimulates APN ( 24 ).…”
Section: Discussionmentioning
confidence: 99%